Tinjauan Hukum Ekonomi Syariah Terhadap Praktek Pre Order Album Kpop Pada Akun Instagram “Allaboutmerch.Kpop” - Rossy Akbar Fitriana; Masjupri (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2022)
Kpop album pre-order is buying and selling music albums from South Korea by ordering and paying in advance. Instagram account “allaboutmerch.kpop”, an that pre-orders kpop albums, but there are several pre-order albums with incomplete specifications. The purposes of this study are to find out the practice of buying and selling pre-order kpop albums on "Allaboutmerch.kpop" Instagram account, and find out the perspective of Syaria Economic Law on the practice of pre-ordering kpop albums on "Allaboutmerch.kpop" Instagram account. This research method used is qualitative research with field research methods. The data sources used are primary and secondary data. Data collection techniques were observation, interviews and documentation. The data analysis uses Miles and Huberman model are data reduction, data presentation and drawing conclusions. The results of the study show that the practice of buying and selling pre-orders on the Instagram account “allaboutmerch.kpop” is a type of buying and selling istiṣna’, based on the object namely albums, in every post on the Instagram account “allaboutmerch.kpop” there are several pre-order albums that do not have the same specifications. So that after being analyzed based on a review of sharia economic law, this sale and purchase didn’t fulfill the terms and conditions to the fullest